Vilnius and the Problem of Rococo, 1803–1830 - Tomasz Jędrzejewski (Literatūra (Vilnius))
Post-partition Vilnius has often been described as the birthplace of Romanticism (or the city of late Enlightenment). This article focuses not on Classicism or Romanticism, but on the local Rococo culture that flourished between 1803 and 1830. The term ‘Rococo’ encompasses a certain aesthetic sensibility that became popular in the salons mondains of the long 18th century. The preference for the small, the irregular, the intriguing and the enchanting can be observed not only in the metropolises such as Paris, Rome, London or Warsaw, but also in Vilnius at the beginning of the 19th century. The author of the article presents the local Rococo culture on the basis of three examples: the periodical Tygodnik Wileński (1804), selected book publications from the early 1820s, and the activities of youth societies (Philomaths, Filarets, and ‘promieniści’ [‘Radiants’]).